Colorimetric-fluorescence-catalysis three-signal microsphere label as well as preparation method and application thereof

By assembling fluorescent quantum dots and iron nanoparticles using large-pore dendritic silica microsphere templates and covering the ZIF-8 shell-loaded platinum nanoparticles, forming nanomicrospheres with colorimetric, fluorescence and catalytic signal outputs, solving the problem that the internal space of the template is not effectively utilized and the material performance is unstable in the prior art, and efficient multimodal detection performance is achieved.

CN119592319AActive Publication Date: 2025-03-11ZHEJIANG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411722828.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing multi-layer assembly structure based on rigid non-porous templates has problems when assembling nanounits that the internal space of the template is not effectively utilized and the number of nanounits is limited. The volatility-induced self-assembly is easily affected by local temperature fluctuations and solvent evaporation rate, resulting in unstable material performance.

Method used

Dendritic silica microspheres with large pore sizes are used as templates, red fluorescent quantum dots and oil-phase iron nanoparticles are first assembled, then bioaffinity micropore ZIF-8 shell is coated, and platinum nanoparticles are loaded on the outer layer to form "litchi-like" nanospheres, achieving the output of colorimetric, fluorescence and catalytic three signals.

Benefits of technology

It improves the fluorescence and colorimetric properties of the material, while maintaining good dispersion and catalytic activity, enhancing the overall performance and versatility of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592319A_ABST
    Figure CN119592319A_ABST
Patent Text Reader

Abstract

The invention discloses a'colorimetric-fluorescence-catalysis' three-signal microsphere label and a preparation method and application thereof.The preparation method comprises the steps that dendritic silicon dioxide microspheres dSiO2 with the large aperture are used as a template, oil-phase quantum dots rQDs are assembled firstly, then oil-phase iron nanoparticles Fe3O4 are assembled, and the oil-phase quantum dots rQDs and the oil-phase iron nanoparticles Fe3O4 are combined to obtain the colorimetric-fluorescence-catalysis three-signal microsphere label. Then coating a layer of biocompatible microporous ZIF-8 shell layer, and loading platinum nanoparticles Pt on the outer layer of the biocompatible microporous ZIF-8 shell layer, so as to obtain a ''litchi sample'' nano microsphere-SQF (at) ZIF-8 / Pt. The SQF (at) ZIF-8 / Pt material disclosed by the invention can be used for constructing a colorimetric-fluorescence-catalysis three-function signal probe, and rQDs and Fe3O4 are used for respectively providing a fluorescence signal and a colorimetric signal. The probe can detect the antigen concentration in colorimetric, ultraviolet and catalytic modes, compared with a single detection mode, the three detection modes have the advantages that signals can be mutually verified, the accuracy is improved, and the probe has naked eye qualitative and multiple quantitative modes and is convenient for a user to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a "colorimetric-fluorescence-catalytic" three-signal microsphere label and a preparation method and application thereof. Background Art

[0002] Lateral flow immunoassay (LFIA) as an in vitro diagnostic tool has made significant progress in the past few decades because it meets the ASSURED criteria published by the World Health Organization (WHO) (affordable, sensitive, specific, user-friendly, rapid and durable, no equipment or simple, and deliverable to end users). However, traditional LFIA labeled with gold nanoparticles (GNPs) relies on a single signal output and may face challenges such as insufficient sensitivity, limited detection range, and susceptibility to external interference, which limits its widespread application. Experimental parameters, environmental changes, and batch-to-batch differences inevitably affect the detection performance of traditional single-modality LFIA. In contrast, multimodal LFIA achieves multi-signal output of detection results by integrating multiple signal sensing modes, which has the following advantages: First, by combining the unique advantages of each mode, multimodal LFIA circumvents the inherent limitations of a single signal sensing mode and helps achieve high-performance detection. Second, multimodal LFIA can provide multiple signal outputs, which is more attractive than traditional LFIA with only a single signal. Third, the signals generated by multimodal LFIA are independent and do not interfere with each other, which allows self-verification and self-correction to improve reliability. Fourth, multimodal LFIA integrates a qualitative mode based on the naked eye and multiple quantitative modes, allowing users to select the appropriate mode according to the available equipment and operating conditions, thereby further improving flexibility. Fifth, different signal output modes differ in sensitivity, linear range, signal acquisition, and procedures, so users can skillfully select the appropriate output signal according to the specific application scenario to achieve the best analytical performance. Therefore, it is highly desirable to develop a multimodal LFIA to ensure reliable and accurate detection performance.

[0003] Multifunctional composite nanomaterials, composed of different functional components, have attracted increasing attention due to their excellent comprehensive performance and broad application prospects in the analytical field. Rational design and synthesis of excellent multifunctional nanohybrid systems can not only combine the inherent properties of different nanomaterials, but also enhance the physical and chemical properties through synergistic interactions between various components. Currently, many synthetic methods for multifunctional nanocomposites have been reported, such as in situ growth strategy, layer-by-layer assembly, template-guided assembly method, and volatilization-induced self-assembly.

[0004] Seed-mediated growth is used to epitaxially grow on the surface of core nanoparticles, allowing the synthesis of shells with different thicknesses to tune the optical properties of multifunctional nanocomposites. The concentration of the precursor needs to be well controlled during the preparation process to avoid additional nucleation. For example, Ju et al. prepared bimetallic Pd@IrNPs with "colorimetric-catalytic" dual functions using a seed-mediated growth method and evaluated the catalytic performance by adjusting the thickness of the Ir shell layer.

[0005] In the process of manufacturing multifunctional composite materials, most nanocomposites that do not require lattice matching and similar chemical properties between substances can be self-assembled layer by layer through organic molecular chains or silica layers. Generally, polymer chains containing groups such as –COOH, –PO3H, –SH, and –NH2 are selected to modify the surface of nanoparticles, and then another functional component is attached by electrostatic adsorption or covalent bonding (such as Au–S bonds) to obtain composite nanoparticles with different functions. For example, Lai et al. used the unique surface viscosity of polydopamine (PDA) to make Pd / Pt bimetallic nanocages uniformly and stably dispersed on the surface of Fe4O3 cores, giving the material both magnetic and catalytic functions. The SiO2 layer with easily modified surface can be used as an intermediate layer. Zeng et al. deposited a layer of iron oxide (Fe3O4) on CsPbBr3 perovskite quantum dots through a silica layer to achieve enhanced target enrichment and signal intensity.

[0006] Current multilayer assembly structures are mainly based on rigid templates, such as common non-porous templates such as polystyrene latex or silica microspheres. Volatility-induced self-assembly can co-assemble multifunctional components in micelles or silica nanocarriers to prepare composite nanomaterials with high loading density.

[0007] Although a variety of methods for synthesizing multifunctional nanocomposites have been reported, there is an obvious problem in assembling nanounits using multilayer assembly structures based on rigid non-porous templates: the internal space of the template is not effectively utilized, and the number of nanounits that can be assembled on the outer surface of the template is limited. In addition, the volatilization-induced self-assembly process is easily affected by local temperature fluctuations and uneven solvent evaporation rates, which may cause inorganic compounds of different properties to be randomly distributed in the synthesized coating structure, thereby affecting the overall performance of the material.

[0008] In the development of multimodal lateral flow immunoassays (LFIA), a key point is the rational design of multifunctional signal tags. These tags are usually composed of multiple components, each of which contributes to the output signal of the multimodal LFIA. Therefore, selecting primitive materials with different functions and precisely controlling their spatial location and quantity are crucial to realize efficient multimodal LFIA. Summary of the invention

[0009] In view of the above technical problems existing in the prior art, the purpose of this application is to provide a "colorimetric-fluorescence-catalytic" three-signal microsphere label and its preparation method and application. The present invention provides a "lychee-like" nano-microsphere - SQF@ZIF-8 / Pt, which is composed of a dendritic silica microsphere (dSiO2) with a large pore size as a template, first assembling oil phase quantum dots (rQDs), then assembling oil phase iron nanoparticles (Fe3O4), and then coating a layer of bio-affinity microporous ZIF-8 shell and loading platinum nanoparticles (Pt) on its outer layer. The large-pore dendritic dSiO2 can fully assemble rQDs as a template to improve the fluorescence intensity of the material; Fe3O4 NPs can not only provide colorimetric signals but also provide magnetic ability and peroxidase-like activity, and the molar absorption coefficient of Fe3O4NPs is low, which will not cause serious quenching of quantum dots. As a porous material, ZIF-8 has excellent adsorption capacity. The adsorbed PtNPs can have a synergistic catalytic effect with the Fe3O4 NPs inside the sphere. As an intermediate layer between Fe3O4 and Pt, it can effectively reduce the magnetic effect of Pt on iron. The synthesis conditions are mild and will not quench the internal quantum dots.

[0010] The technical solution adopted by the present invention is as follows:

[0011] A method for preparing a "colorimetric-fluorescence-catalytic" three-signal microsphere label, using a dendritic silica microsphere dSiO2 with a large pore size as a template, firstly performing thiol modification on the dSiO2 template to obtain dSiO2-SH, firstly assembling red fluorescent quantum dots CdSe / CdS / ZnS, i.e. rQDs, on the dSiO2-SH to obtain a thiol-modified silica sphere / red quantum dot assembly SQ, then assembling oil-phase Fe3O4 nanoparticles with oleic acid ligands on the surface to obtain an assembly SQF; then coating with a layer of bioaffinity microporous ZIF-8 shell, and loading platinum nanoparticles on the outer layer to obtain a "litchi-like" nanosphere SQF@ZIF-8 / Pt, and the preparation is completed.

[0012] Furthermore, the process of thiol modification of the dSiO2 template is as follows: the dSiO2 template is dispersed in ethanol at a concentration of 0.5-1.5 mg / mL, ammonia water and 3-mercaptopropyltrimethoxysilane are added to the obtained dSiO2 ethanol solution, the reaction is stirred at room temperature for 10-15 hours, the precipitate is collected by centrifugation, and washed to obtain the thiol product dSiO2-SH; wherein the mass fraction of ammonia water is 25-30%, the volume fraction of ammonia water in the overall reaction system is 1.0-1.5%, and the volume fraction of 3-mercaptopropyltrimethoxysilane in the overall reaction system is 0.08-0.12%.

[0013] Furthermore, the process of assembling quantum dots rQDs with dSiO2-SH is as follows: adding dSiO2-SH to a solution containing red fluorescent quantum dots CdSe / CdS / ZnS, i.e. rQDs, ultrasonicating at room temperature for 5-30 minutes, and after the assembly is completed, centrifuging and removing the supernatant to obtain a thiol-modified silicon sphere / red quantum dot assembly SQ; the concentration of the rQDs solution is 5-15 mg / mL, and the mass ratio of dSiO2-SH to rQDs is 1:0.8-1.2.

[0014] Furthermore, the preparation method of the oil-phase Fe3O4 nanoparticles includes: adding iron salt, dodecanediol, dibenzyl ether, oleic acid and oleylamine to a reaction bottle, dissolving the solid by ultrasound, filling nitrogen to completely replace the air in the reaction bottle, heating to 180-200°C and vigorously stirring for 20-40 minutes, then continuing to heat to 285-300°C, stirring for 1-3 hours, and then ending the reaction; after cooling to room temperature, adding methanol to the crude solution to precipitate the magnetic particles generated by the reaction, magnetic separation, absorbing the supernatant, adding chloroform to the precipitate to dissolve the magnetic particles, adding methanol again to precipitate the particles, and finally dissolving the precipitate and storing it in toluene for standby use;

[0015] In the preparation method of the oil-phase Fe3O4 nanoparticles, the iron salt is ferric acetylacetonate, and the feed ratio of the iron salt, dodecanediol, dibenzyl ether, oleic acid and oleylamine is (0.6-0.8) g: (1.8-2.4) g: (8-12) mL: (3-5) mL: (3-5) mL.

[0016] Furthermore, the process of assembling the oil phase Fe3O4 nanoparticles by the assembly SQ is as follows:

[0017] 1) Dispersing the assembly SQ in an ethanol solution of polyethyleneimine PEI, stirring the reaction at room temperature for 1-3 hours, and washing the product by centrifugation with ethanol after the reaction is completed; wherein the mass ratio of the dSiO2 microsphere template to polyethyleneimine PEI in the assembly SQ is 1.2-1.5:1;

[0018] 2) The product of step 1) and the oil phase Fe3O4 nanoparticles are dispersed in toluene, ultrasonicated at room temperature for 5-20 minutes, and the product assembly SQF is separated by centrifugation after the structure is assembled; wherein the mass ratio of the oil phase Fe3O4 nanoparticles of step 2) to the dSiO2 microsphere template in the assembly SQ of step 1) is 0.8-1.2:1.

[0019] Furthermore, before coating the ZIF-8 shell, the SQF assembly further includes the following steps: the SQF assembly is dispersed in a chloroform solution containing 5-15 mg / mL PVP, and the reaction is stirred at room temperature for 20-30 hours to replace the oleic acid ligand on the surface of Fe3O4 with PVP, and the assembly is precipitated with hexane after the reaction is completed, and then the assembly is washed to remove excess PVP to obtain a SQF-PVP product;

[0020] The process of SQF-PVP product coating ZIF-8 shell is as follows: SQF-PVP, Zn(NO3)2·6H2O and 2-MeIM are dispersed in methanol together, and reacted at 200-400rpm on a shaker at room temperature for 2-4 hours; after the reaction, it is centrifuged and washed with methanol to obtain the product SQF@ZIF-8; wherein, the molar ratio of Zn(NO3)2·6H2O and 2-MeIM is 1:5-10, and the ratio of the total amount of Zn(NO3)2·6H2O and 2-MeIM to the mass of SQF-PVP is 0.4-0.6:10, the unit of amount of substance is mmol, and the unit of mass is g.

[0021] Furthermore, the loading amount of Pt on SQF@ZIF-8 / Pt is 1%-10%.

[0022] The application of the "colorimetric-fluorescence-catalytic" three-signal microsphere label in the new crown N protein antigen, the application method comprises the following steps:

[0023] 1) Make a test strip: The test strip consists of three parts: a sample pad, an NC membrane, and absorbent paper. The T line on the NC membrane is coated with the capture antibody Ab2 of the new coronavirus n protein, and the C line is coated with goat anti-mouse IgG, and then dried for use; after the test strip assembly is assembled and cut, a test strip product for detection is obtained;

[0024] 2) Preparation of probe SQF@ZIF-8 / Pt-Ab1: Add the new coronavirus N protein labeled antibody to a solution containing the "litchi-like" nanospheres SQF@ZIF-8 / Pt. The mass of the new coronavirus N protein labeled antibody is 1-3% of the mass of SQF@ZIF-8 / Pt. React at room temperature for 2-4 hours, and block with a solution containing 0.5% BSA + 0.1% casein for 2-3 hours. After the reaction, wash with PBST buffer to obtain the probe SQF@ZIF-8 / Pt-Ab1;

[0025] 3) Detection of COVID-19 N protein antigen concentration and preparation of standard curve:

[0026] S1: The SARS-CoV-2 N protein antigen was diluted with loading buffer to prepare a series of antigen standard solutions with different antigen concentrations; each antigen standard solution was tested by adding the probe SQF@ZIF-8 / Pt-Ab1, incubating at room temperature for 3-10 minutes, removing the supernatant after magnetic separation, and resuspending in loading buffer. The obtained sample solution was dripped onto the sample pad of the test strip, and after chromatography for 10-30 minutes, the signal was detected;

[0027] S2: According to the operation process of step S1, make a standard curve of at least one of the following three modes:

[0028] ① Colorimetric mode: When the signal is detected after 10-30 minutes of chromatography in step S1, a camera is used to take a picture under daylight to obtain the colorimetric signal of the test strip. According to this process, the standard curve in the colorimetric mode is drawn with the antigen concentration as the horizontal axis and the gray value of the T line under the colorimetric signal of the test strip as the vertical axis;

[0029] ② Fluorescence mode: When the signal is detected after 10-30 minutes of chromatography in step S1, a fluorescence mode photo is taken under the irradiation of ultraviolet light in a dark environment. According to this process, the standard curve in the fluorescence mode is drawn with the antigen concentration as the horizontal axis and the T line R value in the fluorescence mode photo of the test strip as the vertical axis;

[0030] ③ Catalytic mode: When performing signal detection after 10-30 minutes of chromatography in step S1, add AEC colorimetric solution and H2O2 solution to the NC membrane of the test strip and react for 20-60 minutes. After terminating the AEC colorimetric reaction with pure water, record the catalytic mode signal with a camera under daylight. According to this process, draw a standard curve under the catalytic mode with the antigen concentration as the horizontal coordinate and the gray value of the T line under the catalytic mode signal of the test strip as the vertical coordinate;

[0031] 4) When performing actual sample solution testing, referring to the detection process of step 3), the antigen concentration detection result in at least one of the three modes of colorimetric mode, fluorescence mode, and catalytic mode can be obtained.

[0032] Furthermore, the loading buffer is a pH=7.4 PB buffer containing 1% BSA+1% Tween-20.

[0033] The key points of the present invention are:

[0034] 1. Dendritic silica microspheres with large pores were used as templates to assemble rQDs and Fe3O4 in sequence, which gave the material fluorescent properties as well as magnetic, colorimetric, and catalytic properties.

[0035] 2. Fe3O4 itself has a low absorbance, and its inherent chromaticity and catalytic activity are insufficient, resulting in relatively low detection sensitivity at the μg / mL and ng / mL levels. In order to improve the brightness of the colorimetric signal of Fe3O4, a layer of 2.5 nm PtNPs was adsorbed on the outer layer of ZIF-8.

[0036] 3. Growing a layer of ZIF-8 on the outer layer of Fe3O4 can not only reduce the magnetic shielding effect of the outer layer PtNPs on Fe3O4, but the pores of ZIF-8 itself are also conducive to the diffusion of catalytic substrates inside and outside the ZIF-8 layer.

[0037] 4. Use smaller Pt NPs (2.5 nm). Pt nanoparticles with a size of 2-3 nm have better catalytic activity.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. Most of the best existing technologies related to the second item cover one or two signal tags, and their versatility is limited. The present invention prepares a nano-microsphere with three signal tags of "colorimetric-fluorescent-catalytic", which improves the versatility of practical applications.

[0040] 2. Large-pore dendritic silica can be used as a template to assemble a large number of quantum dots and iron oxide nanoparticles, effectively improving the fluorescence and colorimetric properties of the material while maintaining good dispersibility of the material, which is conducive to subsequent practical applications.

[0041] 3. A thin layer of ZIF-8 grows on the outer layer of the nanospheres. The synthesis process is gentle and does not require high temperatures like other MOFs, which protects the fluorescence of the quantum dots. ZIF-8, as a gentle intermediate layer, has a microporous structure and provides a good carrier for the outer layer loaded with Pt nanoparticles, which is conducive to the internal and external dispersion transfer of the catalytic substrate, thereby achieving a synergistic catalytic effect.

[0042] 4. The SQF@ZIF-8 / Pt material of the present invention is a "colorimetric-fluorescence-catalytic" three-functional signal probe, and rQDs and Fe3O4 provide fluorescence and colorimetric signals respectively. The probe of the present invention can detect antigen concentration in colorimetric, ultraviolet and catalytic modes. The significance of the three-mode detection is that the signals of the three detection modes can be mutually verified compared with a single detection mode, which improves accuracy, has qualitative and multiple quantitative modes for naked eyes, and is convenient for users to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a schematic diagram of the synthesis process of SQF@ZIF-8 / Pt of the present invention;

[0044] Figure 2It is a transmission electron microscope image of the product at each stage of Example 1 of the present invention;

[0045] Figure 3 is a scanning electron microscope image of the product at each stage of Example 1 of the present invention;

[0046] Figure 4 is the EDS image of a single SQF@ZIF-8 / Pt in Example 1;

[0047] Figure 5 It is the comparison result of UV absorption performance of five solutions: dSiO2, rQDs quantum dots, oil-phase nano-Fe3O4 particles, Pt NPs, and SQF@ZIF-8 / Pt;

[0048] Figure 6 This is the comparison result of the fluorescence performance of rQDs quantum dots and SQF@ZIF-8 / Pt solutions;

[0049] Figure 7 is the hysteresis loop of Fe3O4 particles and SQF@ZIF-8 / Pt in Example 1;

[0050] Figure 8 It is the UV absorption curve result of different solutions;

[0051] Figure 9a It is the absorbance value result of SQF@ZIF-8 / Pt at 500nm wavelength under different mass concentrations;

[0052] Figure 9b is the fluorescence intensity result of SQF@ZIF-8 / Pt at different mass concentrations;

[0053] Fig.9c It is the absorbance value result at 450nm of SQF@ZIF-8 / Pt at different mass concentrations after the TMB color development reaction was terminated with concentrated sulfuric acid.

[0054] Fig.10 It is a picture of the test strip taken in daylight in the colorimetric mode and a curve showing the relationship between the gray value of the T line under the colorimetric signal of the test strip and the concentration of the new coronavirus N protein antigen;

[0055] Fig.11 It is a fluorescence photograph of the test strip under the irradiation of ultraviolet light in the fluorescence mode, and a curve showing the relationship between the intensity of the T line R value of the test strip and the concentration of the new coronavirus N protein antigen;

[0056] Fig.12 It is a picture of the test strip in the catalytic mode taken under sunlight and a curve showing the relationship between the grayscale value of the T line and the concentration of the COVID-19 N protein antigen under the catalytic mode signal of the test strip;

[0057] Fig.13These are the results of standard curves produced in three modes: colorimetric mode, catalytic mode, and fluorescence mode.

[0058] Fig.14 It is the specific detection result of the test strip for different antigens. DETAILED DESCRIPTION

[0059] The mass concentration of ammonia water in the embodiment of the present invention is 25-28%.

[0060] Embodiment 1:

[0061] 1. Preparation of dendritic mesoporous silica (dSiO2):

[0062] The temperature of the oil bath was set to 80°C, 25 mL of ultrapure water and 68 mg of triethanolamine (TEA) were added to a 50 mL round-bottom flask, and the mixture was stirred in the oil bath for 30 min, followed by the addition of 380 mg of hexadecyltrimethylammonium bromide (CTAB) and 284 mg of sodium salicylate (NaSaI) and continued to stir for one hour. One hour later, 4 mL of tetraethyl silicate (TEOS) was added and the reaction continued for 4 h. After the reaction was completed, the mixture was centrifuged and washed with anhydrous ethanol, and the mixture was stirred and reacted for 6 h in a mixed solution of methanol (50 ml) and hydrochloric acid (3 ml, mass concentration 65%) at 60°C to remove the surfactant remaining in the dendritic silica, and then centrifuged and washed 3 times with anhydrous ethanol to obtain dendritic mesoporous silica dSiO2.

[0063] 2. Preparation of dSiO2-SH:

[0064] Dissolve 180 mg dSiO2 in 200 mL anhydrous ethanol, add 2.5 mL ammonia water and 200 μL 3-mercaptopropyltrimethoxysilane, stir at room temperature for 12 h, wash with anhydrous ethanol by centrifugation after the reaction is completed, and store in 30 mL anhydrous ethanol.

[0065] 3. Preparation of oil phase nano Fe3O4 particles:

[0066] Add 700mg iron acetylacetonate powder, 2.02g dodecanediol, 10mL dibenzyl ether, 4mL oleic acid and 4mL oleylamine into a 50ml three-necked flask and dissolve by ultrasonic. In an anhydrous and oxygen-free environment, heat to 50℃ at a rate of 10℃ / 5min, keep pumping until the bubbles on the liquid surface disappear, and refill with nitrogen to make the reactants in anhydrous and oxygen-free conditions. After the reaction temperature rises to 200℃, keep the temperature unchanged for 30min, then continue to rise to 285℃, and react at this temperature for 2h before the reaction ends. After the three-necked flask is cooled to room temperature, add an appropriate amount of anhydrous methanol solution to the crude liquid to precipitate the particles and wash them with the help of a magnet. Continue to add chloroform solution to the precipitate to dissolve the magnetic particles and repeat the washing. Finally, disperse it in toluene.

[0067] 4. Assembly of red quantum dots (rQDs) and Fe3O4:

[0068] Assembly of rQDs: Take 20 mg of dSiO2-SH and add 2 mL of rQDs (10 mg / mL) toluene solution, where rQDs are red fluorescent quantum dots CdSe / CdS / ZnS. Assemble in an ultrasonic environment for 10 min at room temperature. After the assembly is completed, centrifuge and remove the supernatant to obtain the thiolated silicon sphere / red quantum dot assembly SQ.

[0069] Assembly of Fe3O4: The product SQ obtained in the previous step was dispersed in 40ml ethanol solution containing 14mg of polyethyleneimine (PEI), and stirred at room temperature for 2h. After centrifugation and washing with ethanol three times, it was added to 2mL toluene, and 20mgFe3O4 was added and assembled in an ultrasonic environment, and ultrasonication was performed at room temperature for 7min. After the assembly was completed, the assembly SQF was obtained, and SQF was dispersed in 60ml chloroform solution containing 600mg PVP (Mw=10000) (the purpose of replacing the oleic acid ligand with PVP is to facilitate the next step of growing ZIF-8), and stirred at room temperature for 24h to replace the oleic acid ligand on the surface of Fe3O4 with PVP. After the reaction, the assembly was precipitated with hexane, and the excess PVP was washed by centrifugation with a mixture of n-hexane and chloroform in a volume ratio of 1:1. The product was stored in anhydrous methanol, and the final product was marked as SQF-PVP.

[0070] 5. Preparation of PtNPs:

[0071] At room temperature, 533 mg of polyvinyl pyrrolidone (PVP, Mw = 24000) was added to 180 mL of anhydrous methanol and H2PtCl6·6H2O (6.0 Mm 20 ​​mL) aqueous solution. The mixed solution was refluxed at 70 ° C for 3 h. The methanol was removed by a rotary evaporator, and the nanoparticles in the remaining solution were precipitated by acetone, and then centrifuged and washed with a mixture of chloroform and n-hexane in a volume ratio of 4:1 at 6000 rpm for 5 min to remove excess PVP. The PtNPs product was stored in 20 mL of anhydrous methanol.

[0072] The PtNPs prepared in step 5 were characterized by TEM and SEM, and the average particle size was 2.5 nm.

[0073] 6. Outer layer growth of ZIF-8 and modification of Pt NPs:

[0074] Take 10 mg of SQF-PVP and disperse it in 10 mL of anhydrous methanol. Then add 1 mL of Zn(NO3)2·6H2O (0.0672 mM) methanol solution and 4 mL of 2-MeIM (0.1073 mM) methanol solution in sequence. The reaction was carried out at room temperature with a shaker at 300 rpm for 3 h. The reaction was completed and washed three times by centrifugation with methanol to obtain the SQF@ZIF-8 product.

[0075] Adsorption of PtNPs: 10 mg of SQF@ZIF-8 was dispersed in 10 mL of anhydrous methanol, and then 0.5 ml of Pt NPs solution (containing about 1 mg of PtNPs) was added and stirred for adsorption for 6 hours under nitrogen protection. Finally, the mixture was centrifuged and washed to obtain the "litchi-like" nanosphere SQF@ZIF-8 / Pt target product.

[0076] The performance tests were performed on the products of each stage of Example 1:

[0077] 1) Transmission electron microscope images of the products of each stage of Example 1 of the present invention are shown in Figure 2 middle, Figure 2 Figures a1-e1 correspond to the transmission electron microscopy images of dSiO2, SQ, SQF, SQF@ZIF-8, and SQF@ZIF-8 / Pt, respectively. Figure 2 It can be seen that with the assembly of rQDs and Fe3O4, the holes of the dendritic silicon spheres become smaller and smaller. Figure 2 Figure d1 shows the growth of ZIF-8. Figure 2 Figure e1 shows that Pt particles are adsorbed on ZIF-8.

[0078] The scanning electron microscope images of the products of each stage of Example 1 of the present invention are shown in Figure 3 , Figure 3 Figures a2-e2 show the scanning electron microscope images of SiO2, SQ, SQF, SQF@ZIF-8, and SQF@ZIF-8 / Pt, respectively, showing the specific morphology of the materials at different synthesis stages. As the primitives are filled, the pores of the dendritic silicon become smaller and smaller, indicating that the internal pores of the dendritic silicon are gradually occupied.

[0079] 2) Example 1 EDS diagram of a single SQF@ZIF-8 / Pt is shown in Figure 4 , EDS images show the elements contained in SQF@ZIF-8 / Pt.

[0080] 3) Prepare dilute solutions of 2 mg / mL for dSiO2, rQDs quantum dots, oil-phase nano Fe3O4 particles, PtNPs, and SQF@ZIF-8 / Pt in Example 1. The solvent for preparing the solutions of dSiO2, Pt NPs, and SQF@ZIF-8 / Pt is anhydrous methanol, and the solvent for preparing the solutions of rQDs quantum dots and Fe3O4 particles is toluene. The normalized results of the UV absorption curves of the five solutions of dSiO2, rQDs quantum dots, oil-phase nano Fe3O4 particles, PtNPs, and SQF@ZIF-8 / Pt are shown in Figure 5 ,in addition Figure 5 The middle inset corresponds to the photographs of the five solutions under daylight. Figure 5 Characterizes the colorimetric properties of the material. Figure 5 It can be seen that the UV absorption spectrum of SQF@ZIF-8 / Pt covers the UV characteristic absorption peaks of rQDs, Fe3O4, and Pt.

[0081] 4) Prepare dilute solutions of rQDs quantum dots and SQF@ZIF-8 / Pt in Example 1 with a concentration of 2 mg / mL, respectively. The solvent for the rQDs quantum dots solution is toluene, and the solvent for the SQF@ZIF-8 / Pt solution is anhydrous methanol. The results of the normalized fluorescence intensity curves of the rQDs quantum dots and SQF@ZIF-8 / Pt solutions are shown in Figure 6 In, from Figure 6 It can be seen that SQF@ZIF-8 / Pt has excellent fluorescence properties. Figure 6 The illustrations are, from left to right, photographs of rQDs solution under sunlight and UV light, and photographs of SQF@ZIF-8 / Pt solution under sunlight and UV light.

[0082] from Figure 6 It can be seen that although SQF@ZIF-8 / Pt assembled iron oxide particles after assembling quantum dots, as well as the subsequent growth of ZIF-8 and the adsorption of Pt, it did not affect its fluorescence performance. The fluorescence spectrum of SQF@ZIF-8 / Pt was only slightly blue-shifted compared to pure rQDs, indicating that SQF@ZIF-8 / Pt has excellent fluorescence properties.

[0083] 5) The hysteresis loops of Fe3O4 particles and SQF@ZIF-8 / Pt in Example 1 are shown in Figure 7 , characterized the magnetic properties of the material. The magnetic saturation intensity of SQF@ZIF-8 / Pt is lower than that of pure Fe3O4 because the amount of assembled Fe3O4 is limited. This proves that the material has excellent magnetic separation function and can use magnetic separation to clean impurities in the sample.

[0084] 6) Prepare the following solution:

[0085] TMB was dissolved in DMSO to obtain a 1 mM TMB solution. SQF, SQF@ZIF-8, and SQF@ZIF-8 / Pt were prepared with methanol as solvent to obtain solutions with a concentration of 0.1 mg / ml.

[0086] ①TMB+H2O2 solution: 1mM TMB solution and 2M H2O2 aqueous solution are mixed in a volume ratio of 1:1.

[0087] ②TMB+H2O2+SQF@ZIF-8 solution: 1 mM TMB solution, 2 M H2O2 aqueous solution, and 0.1 mg / ml SQF@ZIF-8 solution were mixed in a volume ratio of 2:3:1.

[0088] ③TMB+H2O2+SQF solution: 1mM TMB solution, 2M H2O2 aqueous solution, and 0.1mg / ml SQF solution are mixed in a volume ratio of 2:3:1.

[0089] ④TMB+H2O2+SQF@ZIF-8 / Pt solution: 1 mM TMB solution, 2 M H2O2 aqueous solution, and 0.1 mg / ml SQF@ZIF-8 / Pt solution were mixed in a volume ratio of 2:3:1.

[0090] The UV absorption curves of the above four solutions No. ①-④ are shown in Figure 8 , Figure 8 The middle illustration is a photograph of the four solutions after reacting at room temperature for 2 minutes. The illustrations correspond to the four solutions numbered ①-④ above from left to right.

[0091] from Figure 8 It can be seen that when only TMB and H2O2 are present, due to the insufficient oxidation ability of H2O2, no peak at 652nm (the ultraviolet characteristic absorption peak of oxidized TMB) is observed from the UV spectrum; when SQF is added, a peak is observed at 652nm, proving that SQF has peroxidase-like activity; when SQF@ZIF-8 is added, the peak at 652nm becomes weaker because ZIF-8 does not have peroxidase-like activity; after adding SQF@ZIF-8 / Pt, the absorption peak at 652nm is significantly enhanced, indicating that SQF@ZIF-8 / Pt has excellent peroxidase activity.

[0092] 7) The absorbance values ​​of methanol solutions of SQF@ZIF-8 / Pt at 500 nm are shown in Table 1. Figure 9a , fluorescence intensity see Figure 9b .

[0093] 1mM TMB solution, 2M H2O2 aqueous solution and different concentrations of SQF@ZIF-8 / Pt methanol solution were mixed in a volume ratio of 2:3:1 and color development was carried out at room temperature for 30 minutes. After that, the TMB color development reaction was terminated with concentrated sulfuric acid. The absorbance value at 450nm was shown in Figure 2. Fig.9c .

[0094] Figure 9a-9c It can be seen that the signal responses of the colorimetric, fluorescent and catalytic signals of SQF@ZIF-8 / Pt in the solution at the same mass concentration are different, indicating that SQF@ZIF-8 / Pt has three different sensitivity signals.

[0095] The capture antibody (Ab2) of the new crown N protein, the new crown N protein labeling antibody Ab1 and the new crown N protein antigen SARS-Cov-2 NP used in Example 2 of the present invention are all from Nanjing Baikang Biotechnology Co., Ltd. Antigens Flu A, Flu B, MP, and HRSV are all from Feipeng Bio, and Human IgG is from Lianke Bio.

[0096] Embodiment 2:

[0097] The "litchi-like" nano-microsphere SQF@ZIF-8 / Pt target product finally prepared in Example 1 was used for antigen detection, and the experimental steps were as follows:

[0098] 1) The test strip consists of three parts: a sample pad, an NC membrane, and absorbent paper. The sample pad is treated with 20mM PB7.4 buffer (containing 0.5% BSA, 0.1% sodium caseinate, 3% trehalose, 1% Tween-20, and 0.2% PVP24000) in advance and dried for use; the T line on the NC membrane is coated with the capture antibody (Ab2) of the new crown N protein, and the C line is coated with sheep anti-mouse IgG and dried for use; after the test strip assembly is assembled and cut, it can be used for the detection of the new crown N protein.

[0099] 2) Preparation of SQF@ZIF-8 / Pt-Ab1: Add 10 μg of the new coronavirus N protein-labeled antibody Ab1 to 500 μl of a solution containing 500 μg of SQF@ZIF-8 / Pt, react at room temperature for 3 hours, and add a final concentration of 0.5% BSA + 0.1% casein to block for 2.5 hours. After the reaction is completed, wash twice with PBST buffer (i.e., PBS buffer containing 0.05% Tween 20), store in PBST, and store in a refrigerator at 4°C.

[0100] 3) Detection steps:

[0101] S1: The SARS-Cov-2 N protein antigen (i.e., SARS-Cov-2 NP) was diluted with a loading buffer (10 mM PB buffer with pH = 7.4 + 1% BSA + 1% Tween-20), and the SARS-Cov-2 antigen was diluted into a series of concentration gradients (0, 0.025, 0.050, 0.1, 0.25, 0.5, 1, 2.5, 5, 10, 25, 50, 100, 250, 500 ng / ml), and 8 μg of the probe prepared in step 2) was added. The mixture was incubated at room temperature for 5 minutes, and the supernatant was removed after magnetic separation for 10 minutes. The sample solution was resuspended in the loading buffer to obtain the sample solution, and the sample solution was dripped onto the sample pad of the test strip. After chromatography for 15 minutes, the signal was detected;

[0102] S2: According to the operation process of step S1, make a standard curve of at least one of the following three modes:

[0103] ① Colorimetric mode: When the signal is detected after 15 minutes of chromatography in step S1, a camera is used to take a picture under daylight to obtain the colorimetric signal of the test strip. According to this process, the standard curve in the colorimetric mode is drawn with the antigen concentration as the horizontal axis and the gray value of the T line under the colorimetric signal of the test strip as the vertical axis;

[0104] ② Fluorescence mode: When the signal is detected after 15 minutes of chromatography in step S1, a fluorescence mode photo is taken under the irradiation of ultraviolet light in a dark environment. According to this process, the standard curve in the fluorescence mode is drawn with the antigen concentration as the horizontal axis and the T line R value in the fluorescence mode photo of the test strip as the vertical axis;

[0105] ③ Catalytic mode: When performing signal detection after 15 minutes of chromatography in step S1, 30 μl of AEC color development solution and 20 μl of 2MH2O2 solution were added dropwise to the NC membrane of the test strip for reaction for 30 minutes. After terminating the AEC color development reaction with pure water, the catalytic mode signal was recorded with a camera under daylight. According to this process, a standard curve under the catalytic mode was drawn with the antigen concentration as the horizontal coordinate and the gray value of the T line under the catalytic mode signal of the test strip as the vertical coordinate.

[0106] According to the above detection process, the test strip is photographed in the sunlight in the colorimetric mode, and the relationship curve between the gray value of the T line under the colorimetric signal of the test strip and the concentration of the new crown N protein antigen is shown in Fig.10 .

[0107] According to the above detection process, the fluorescent photos of the test strips under the irradiation of ultraviolet light in the fluorescence mode and the relationship curve between the intensity of the T line R value of the test strips and the concentration of the new crown N protein antigen are shown in Fig.11 .

[0108] According to the above detection process, the test strips were photographed in the catalytic mode under sunlight, and the relationship curve between the gray value of the T line and the concentration of the new crown N protein antigen under the catalytic mode signal of the test strips was shown in Figure 2. Fig.12 .

[0109] according to Figure 10-12 The results of the standard curves prepared in the three modes are summarized in Fig.13 middle. Fig.13 In the standard curve results, from left to right, these are the standard curves for the catalytic mode, fluorescence mode, and colorimetric mode. Figure 3 Comparison of the three standard curve results shows that the catalytic mode has the highest sensitivity, followed by the fluorescence mode, and the colorimetric mode is relatively poor.

[0110] In addition, the probe and test strip of Example 2 of the present invention were used to perform specific detection of different antigen solutions in a catalytic mode according to the operating steps of step 1) to step 3) of Example 2. The comparison results of the signal response intensity of different antigen detections are shown in FIG. Fig.14 ,from Fig.14 It can be seen that different antigen interfering substances were not non-specifically recognized, and the signal response intensities of the detection of antigens such as Flu A, Flu B, MP, HRSV, and Human IgG were much smaller than that of the target antigen SARS-Cov-2 NP, indicating that the test strip constructed by the present invention has high specificity.

Claims

1. A method for preparing a "colorimetric-fluorescent-catalytic" three-signal microsphere label, characterized in that Using dendritic silica microspheres dSiO2 with large pores as templates, the dSiO2 template is first thiolated to obtain dSiO2-SH, and the dSiO2-SH is first assembled with red fluorescent quantum dots CdSe / CdS / ZnS, namely rQDs, to obtain the thiolated silica sphere / red quantum dot assembly SQ, and then assembled with oil-phase Fe3O4 nanoparticles with oleic acid ligands on the surface to obtain the assembly SQF; then coated with a layer of bioaffinity microporous ZIF-8 shell, and loaded with platinum nanoparticles on its outer layer to obtain the "lychee-like" nanomicrospheres SQF@ZIF-8 / Pt, and the preparation is completed.

2. The method for preparing a "colorimetric-fluorescent-catalytic" three-signal microsphere label according to claim 1, characterized in that The process of thiolation modification of dSiO2 template is as follows: dSiO2 template is dispersed in ethanol at a concentration of 0.5-1.5 mg / mL, ammonia water and 3-mercaptopropyltrimethoxysilane are added to the obtained dSiO2 ethanol solution, the reaction is stirred at room temperature for 10-15 hours, the precipitate is collected by centrifugation, and washed to obtain the thiolation product dSiO2-SH; wherein the mass fraction of ammonia water is 25-30%, the volume fraction of ammonia water in the overall reaction system is 1.0-1.5%, and the volume fraction of 3-mercaptopropyltrimethoxysilane in the overall reaction system is 0.08-0.12%.

3. The method for preparing a "colorimetric-fluorescent-catalytic" three-signal microsphere label according to claim 1, characterized in that The process of assembling quantum dots rQDs with dSiO2-SH is as follows: adding dSiO2-SH to a solution containing red fluorescent quantum dots CdSe / CdS / ZnS, i.e. rQDs, ultrasonicating at room temperature for 5-30 minutes, and after the assembly is completed, centrifuging and removing the supernatant to obtain a thiol-modified silicon sphere / red quantum dot assembly SQ; the concentration of the rQDs solution is 5-15 mg / mL, and the mass ratio of dSiO2-SH to rQDs is 1:0.8-1.

2.

4. The method for preparing a "colorimetric-fluorescent-catalytic" three-signal microsphere label according to claim 1, characterized in that The preparation method of the oil-phase Fe3O4 nanoparticles comprises: adding iron salt, dodecanediol, dibenzyl ether, oleic acid and oleylamine into a reaction bottle, dissolving the solid by ultrasonication, injecting nitrogen to completely replace the air in the reaction bottle, heating the temperature to 180-200°C and vigorously stirring for 20-40 minutes, then heating the temperature to 285-300°C, stirring for 1-3 hours, and then ending the reaction; cooling to room temperature, adding methanol to the crude solution to precipitate the magnetic particles generated by the reaction, magnetic separation, removing the supernatant, adding chloroform to the precipitate to dissolve the magnetic particles, adding methanol again to precipitate the particles, and finally dissolving the precipitate and storing it in toluene for later use; In the preparation method of the oil-phase Fe3O4 nanoparticles, the iron salt is iron acetylacetonate, and the feed ratio of the iron salt, dodecanediol, dibenzyl ether, oleic acid and oleylamine is (0.6-0.8) g: (1.8-2.4) g: (8-12) mL: (3-5) mL: (3-5) mL.

5. The method for preparing a "colorimetric-fluorescent-catalytic" three-signal microsphere label according to claim 1, characterized in that The process of assembling oil-phase Fe3O4 nanoparticles by the assembly SQ is as follows: 1) Disperse the assembly SQ in an ethanol solution of polyethyleneimine PEI, stir and react at room temperature for 1-3 hours, and wash the product by centrifugation with ethanol after the reaction is completed; wherein the mass ratio of the dSiO2 microsphere template to polyethyleneimine PEI in the assembly SQ is 1.2-1.5:1; 2) The product of step 1) and the oil phase Fe3O4 nanoparticles are dispersed in toluene, ultrasonicated at room temperature for 5-20 minutes, and the product assembly SQF is separated by centrifugation after the structure is assembled; wherein the mass ratio of the oil phase Fe3O4 nanoparticles of step 2) to the dSiO2 microsphere template in the assembly SQ of step 1) is 0.8-1.2:

1.

6. The method for preparing a "colorimetric-fluorescent-catalytic" three-signal microsphere label according to claim 1, characterized in that Before coating the ZIF-8 shell, the SQF assembly further includes the following steps: the SQF assembly is dispersed in a chloroform solution containing 5-15 mg / mL PVP, and the reaction is stirred at room temperature for 20-30 hours to replace the oleic acid ligand on the surface of Fe3O4 with PVP. After the reaction, the assembly is precipitated with hexane, and then the assembly is washed to remove excess PVP to obtain a SQF-PVP product. The process of SQF-PVP product coating ZIF-8 shell is as follows: SQF-PVP, Zn(NO3)2•6H2O and 2-MeIM are dispersed in methanol together, and reacted at 200-400rpm on a shaker at room temperature for 2-4 hours; after the reaction, methanol is used for centrifugal washing to obtain the product SQF@ZIF-8; wherein, the molar ratio of Zn(NO3)2•6H2O and 2-MeIM is 1:5-10, and the ratio of the total amount of Zn(NO3)2•6H2O and 2-MeIM to the mass of SQF-PVP is 0.4-0.6:10, the unit of amount of substance is mmol, and the unit of mass is g.

7. The method for preparing a "colorimetric-fluorescent-catalytic" three-signal microsphere label according to claim 1, characterized in that The Pt loading on SQF@ZIF-8 / Pt is 1%-10%.

8. A "colorimetric-fluorescent-catalytic" triple-signal microsphere label prepared by the method of any one of claims 1 to 7.

9. The use of a "colorimetric-fluorescence-catalytic" three-signal microsphere label in the new crown N protein antigen as claimed in claim 8, characterized in that The application method comprises the following steps: 1) Make a test strip: The test strip consists of three parts: a sample pad, an NC membrane, and absorbent paper. The T line on the NC membrane is coated with the capture antibody Ab2 of the new coronavirus n protein, and the C line is coated with goat anti-mouse IgG, which are then dried for later use. After the test strip assembly is assembled and cut, a test strip product for detection is obtained; 2) Preparation of probe SQF@ZIF-8 / Pt-Ab1: Add the SARS-CoV-2 N protein-labeled antibody to a solution containing "litchi-like" nanospheres SQF@ZIF-8 / Pt. The mass of the SARS-CoV-2 N protein-labeled antibody is 1-3% of the mass of SQF@ZIF-8 / Pt. React at room temperature for 2-4 hours, and block with a solution containing 0.5% BSA + 0.1% casein for 2-3 hours. After the reaction, wash with PBST buffer to obtain the probe SQF@ZIF-8 / Pt-Ab1. 3) Detection of COVID-19 N protein antigen concentration and preparation of standard curve: S1: The SARS-CoV-2 N protein antigen was diluted with loading buffer to prepare a series of antigen standard solutions with different antigen concentrations; each antigen standard solution was tested by adding the probe SQF@ZIF-8 / Pt-Ab1, incubating at room temperature for 3-10 minutes, removing the supernatant after magnetic separation, and resuspending in loading buffer. The obtained sample solution was dripped onto the sample pad of the test strip, and after chromatography for 10-30 minutes, the signal was detected; S2: According to the operation process of step S1, make a standard curve of at least one of the following three modes: ① Colorimetric mode: When the signal is detected after 10-30 minutes of chromatography in step S1, a camera is used to take a picture under daylight to obtain the colorimetric signal of the test strip. According to this process, the standard curve in the colorimetric mode is drawn with the antigen concentration as the horizontal axis and the gray value of the T line under the colorimetric signal of the test strip as the vertical axis; ② Fluorescence mode: When the signal is detected after 10-30 minutes of chromatography in step S1, a fluorescence mode photo is taken under the irradiation of ultraviolet light in a dark environment. According to this process, the standard curve in the fluorescence mode is drawn with the antigen concentration as the horizontal axis and the T line R value in the fluorescence mode photo of the test strip as the vertical axis; ③ Catalytic mode: When performing signal detection after 10-30 minutes of chromatography in step S1, add AEC colorimetric solution and H2O2 solution to the NC membrane of the test strip and react for 20-60 minutes. After terminating the AEC colorimetric reaction with pure water, record the catalytic mode signal with a camera under daylight. According to this process, draw a standard curve under the catalytic mode with the antigen concentration as the horizontal coordinate and the gray value of the T line under the catalytic mode signal of the test strip as the vertical coordinate; 4) When testing the actual sample solution, referring to the detection process in step 3), the antigen concentration detection result in at least one of the three modes of colorimetric mode, fluorescence mode, and catalytic mode can be obtained.

10. The use according to claim 9, characterized in that The loading buffer is a pH=7.4 PB buffer containing 1% BSA+1% Tween-20.

Citation Information

Patent Citations

  • Multi-level controllable assembly type fluorescent-magnetic bifunctional microsphere as well as preparation method and application thereof

    CN111790324A

  • Three-dimensional homogeneous filling type magnetic-noble metal composite nano-enzyme, novel crown antigen immunochromatography test paper thereof and application of three-dimensional homogeneous filling type magnetic-noble metal composite nano-enzyme

    CN115060893A

  • Magnetic nano-enzyme material for colorimetric-fluorescence dual-mode detection of DNA (deoxyribonucleic acid) as well as preparation method and application of magnetic nano-enzyme material

    CN118389645A

  • Nano-composite with dual functions of colorimetry and catalysis as well as preparation method and application of nano-composite

    CN118558367A